2012
DOI: 10.1093/eurheartj/ehs261
|View full text |Cite
|
Sign up to set email alerts
|

Mortality outcome of out-of-hours primary percutaneous coronary intervention in the current era

Abstract: This study of real-world, unselected STEMI patients demonstrates that in a large, well-staffed centre, PPCI outside routine-working hours is safe with no difference in outcome of in-hospital and long-term mortality compared with PPCI during routine-working hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 19 publications
2
29
0
Order By: Relevance
“…These conflicting results may be due to presentation of sicker patients and less successful PCI procedures during off-hours (Glaser et al, 2008). However, a recent study by Noman et al (2012) did not find any differences. In our study, procedural success rates showed no significant differences between the groups, although there was a trend toward lower success rates in group 1.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These conflicting results may be due to presentation of sicker patients and less successful PCI procedures during off-hours (Glaser et al, 2008). However, a recent study by Noman et al (2012) did not find any differences. In our study, procedural success rates showed no significant differences between the groups, although there was a trend toward lower success rates in group 1.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have assessed in-hospital, medium and long-term outcomes for PCI therapy during on-hours compared to off-hours. Distinct longer delay times during off-hours are found in most of these studies, but there are conflicting results in terms of angiographic and clinical outcomes for patients treated during off-hours (Beohar et al, 2001;Berger et al, 2006;Casella et al, 2011;Cubeddu et al, 2013;De Luca et al, 2005;Jneid et al, 2008;Noman et al, 2012;Ortolani et al, 2007;Sadeghi et al, 2004;Saleem et al, 2004;Uyarel et al, 2009;Zahn et al, 1999). These conflicting results may be due to presentation of sicker patients and less successful PCI procedures during off-hours (Glaser et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Our observation of differences in transradial access during IWH and OWH is not new and has been previously reported. 16 It would be interesting to explore the trends in transradial access use, bleeding complications, and mortality over time in other cardiac networks/centers.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] A recent meta-analysis has shown increased mortality in patients undergoing PPCI during OWH. 17 It is difficult to compare these studies because of differences in patient characteristics, treatment(s) provided, and the variable definitions of routine working hours.…”
Section: Ppci During Out Of Working Hoursmentioning
confidence: 99%
See 1 more Smart Citation